The Effectiveness of Acupressure Therapy and Increasing Knowledge of Hypertension Diet in Anjir Serapat Village Muara 1 - S, Evita; Gusdiandi, Hendy; Amalia, Khalisah; Mira, Mira; Ihsan, Radifan (OMNICODE Journal (Omnicompetence Community Developement Journal), 2025)
Hypertension is a common health problem and is known as the "silent killer." Non-pharmacological therapy is an increasingly needed alternative, especially since hypertension medications can cause long-term side effects. This study seeks to ascertain the extent to which hypertension patients' blood pressure is impacted by acupressure therapy and a hypertension diet, as well as the community's level of ability in this area. Anjir Serapat Muara 1 Village's 33 hypertensive residents were the subjects of this research. A single-group pretest-posttest design was employed in the quasi-experimental procedure. The results demonstrated that following treatment, 84.4% of individuals saw a reduction in blood pressure. This treatment has been successful in reducing blood pressure in most individuals with hypertension and can be utilised as an additional intervention in the community's hypertension care.